Hematopoietic Stem Cell Factors: Their Functional Role in Self-Renewal and Clinical Aspects - Mann, Zoya; Sengar, Manisha; Verma, Yogesh Kumar; Rajalingam, Raja; Raghav, Pawan Kumar (Frontiers in Cell and Developmental Biology, 2022)
Hematopoietic stem cells (HSCs) possess two important properties such as self-renewal and differentiation. These properties of HSCs are maintained through hematopoiesis. This process gives rise to two subpopulations, long-term and short-term HSCs, which have become a popular convention for treating various hematological disorders. The clinical application of HSCs is bone marrow transplant in patients with aplastic anemia, congenital neutropenia, sickle cell anemia, thalassemia, or replacement of damaged bone marrow in case of chemotherapy. The self-renewal attribute of HSCs ensures long-term hematopoiesis post-transplantation. However, HSCs need to be infused in large numbers to reach their target site and meet the demands since they lose their self-renewal capacity after a few passages. Therefore, a more in-depth understanding of ex vivo HSCs expansion needs to be developed to delineate ways to enhance the self-renewability of isolated HSCs. The multifaceted self-renewal process is regulated by factors, including transcription factors, miRNAs, and the bone marrow niche. A developed classical hierarchical model that outlines the hematopoiesis in a lineage-specific manner through in vivo fate mapping, barcoding, and determination of self-renewal regulatory factors are still to be explored in more detail. Thus, an in-depth study of the self-renewal property of HSCs is essentially required to be utilized for ex vivo expansion. This review primarily focuses on the HSC self-renewal pathway and evaluates the regulatory molecular factors involved in considering a targeted clinical approach in numerous malignancies and outlining gaps in the current knowledge.